Estimating the impact of agricultural technology on poverty reduction in rural Nigeria - Omilola, Babatunde (International Food Policy Research Institute, 2009)
It has often been argued that new agricultural technologies lead to poverty reduction. This paper argues that any changes in poverty situation attributed to those who adopt new agricultural technology (treatment group) without a counterfactual comparison of carefully selected nonadopters (control group) are likely to be questionable. The paper estimates the effects of new agricultural technology on poverty reduction by employing the “double difference” method on data collected in rural Nigeria. Seeing the agricultural technology–poverty linkage through the lenses of adopters and nonadopters of such new technology provides understanding of the relationship between agricultural technology and poverty. The paper finds that differences in poverty status between adopters and nonadopters of new agricultural technologies (a combination of tube wells and pumps) introduced in rural Nigeria in the late 1980s and early 1990s are alarmingly modest. The paper concludes that new agricultural technology would not expressly lead to poverty reduction in poor countries. The exact channels through which new agricultural technology impact poverty outcomes need to be further explored.